2012
DOI: 10.2174/157488712799363253
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Estrogenic Menopausal Hormone Therapy

Abstract: Cardiovascular disease (CVD) is more common in men and postmenopausal women (Post-MW) than premenopausal women (Pre-MW). Despite recent advances in preventive measures, the incidence of CVD in women has shown a rise that matched the increase in the Post-MW population. The increased incidence of CVD in Post-MW has been related to the decline in estrogen levels, and hence suggested vascular benefits of endogenous estrogen. Experimental studies have identified estrogen receptor ERα, ERβ and a novel estrogen bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 184 publications
2
59
1
11
Order By: Relevance
“…Also, earlier clinical observations suggested that climacteric women receiving E2 containing menopausal hormone therapy (MHT) to reduce menopausal symptoms have lower rates of CVD, supporting the vascular benefits of E2 (Reslan and Khalil, 2012;Gurney et al, 2014). The beneficial vascular effects of E2 have been ascribed to modification of circulating lipoproteins, inhibition of the vascular accumulation of collagen, and vasodilator effects on the endothelium and vascular smooth muscle (VSM) (Mendelsohn, 2002;Khalil, 2013).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, earlier clinical observations suggested that climacteric women receiving E2 containing menopausal hormone therapy (MHT) to reduce menopausal symptoms have lower rates of CVD, supporting the vascular benefits of E2 (Reslan and Khalil, 2012;Gurney et al, 2014). The beneficial vascular effects of E2 have been ascribed to modification of circulating lipoproteins, inhibition of the vascular accumulation of collagen, and vasodilator effects on the endothelium and vascular smooth muscle (VSM) (Mendelsohn, 2002;Khalil, 2013).…”
Section: Introductionmentioning
confidence: 98%
“…Despite evidence from earlier clinical observations and experimental studies, randomized clinical trials in postmenopausal women with or without CVD have shown no vascular benefits from MHT (Reslan and Khalil, 2012;Gurney et al, 2014). Several factors could have contributed to the lack of vascular benefits of MHT, including preexisting CVD, the subject's age, and age-related changes in estrogen receptor (ER) amount, distribution, integrity, and post-ER signaling mechanisms (Reslan and Khalil, 2012;Gurney et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its incidence and mortality is very low in reproductive age women, but it increases with age [12]. Estradiol (E2) reduces the development of the early atherosclerotic lesions, in some measure, by its efects on the lipid metabolism, with a reduction of the lipid deposits from the intima [13].…”
Section: Recent Trends In Cardiovascular Risksmentioning
confidence: 99%
“…The CARDIA Male Hormone Study showed that there are associations of androgens with PA and fitness in young black and white men (Wolin et al 2007). Estrogens have vasculo-protective actions that are thought to prevent atherosclerosis (Reslan and Khalil 2012). Estrogens contribute to the regulation of the delicate balance between fighting infections and protecting arteries from damage, thus lowering the risk of cardiovascular disease (Meyer and Barton 2016).…”
Section: Introductionmentioning
confidence: 99%